A new species of Ninia (Serpentes: Dipsadidae) from Chocó-Magdalena biogeographical province, western Colombia - Angarita-Sierra, Teddy (Zootaxa, 2017)
We describe a new species of the genus Ninia from the Chocó-Magdalena biogeographic province, which was previously reported as a distinct population of N. maculata or as N. atrata from the western slopes of the Cordillera Occidental of Colombia. The new species is similar to N. atrata, N. celata, N. espinali, N. franciscoi, and N. maculata. It shares the following characteristics with the species mentioned above: 19 dorsal scale rows without reductions; dorsal ground color black or dark brown; white or cream occipital nuchal collar. However, it is easily distinguished from all other congeners because it has a non-regular color pattern in the ventral surfaces of the head and body, subcaudal surface homogeneously black or dark brown, two nasal scales, and one lateral projection ornamented with a large basal hook-shaped spine that is larger than any other spine on the hemipenial body. The presence of a lateral projection on the hemipenial body makes the new species the only member of the genus from South America that shares this feature with its Central American congeners. This feature suggests a closer relationship with this linage. Finally, our results indicate that proper and careful revision of the Ninia atrata species complex will help to understand and clarify the taxonomic composition of the genus.